Removal of Nickel-63 Ions from Aqueous Solutions by Chitosan Flakes - M. Zamin; T. Shaheen; M. Ahmed (Adsorption Science & Technology)
Radiotracer batch equilibrium experiments were undertaken to check the uptake of nickel-63 from aqueous solutions by a natural polymer, i.e. chitosan obtained from fishery wastes (shrimp, crab and prawn shells). The results of kinetic and equilibrium studies showed significant removal of 63 Ni by chitosan with the uptake being pH-dependent. The experimental adsorption data obtained for aqueous solutions containing 63 Ni metal ions were found to correlate well with the Langmuir, Freundlich and Dubinin-Radushkevich (D-R) isotherm equations. The following parameters were obtained: Freundlich: 1/n = 0.57 ± 0.02; A = 0.105 ± 0.003 mmol/g; Langmuir: Q = 0.2 ± 0.14 μmol/g; b = 128.47 ± 0.56 dm 3 /mol; D-R: β = −0.0043 kJ 2 /mol 2 ; C m = 0.16 mmol/g; E = 10.78 ± 0.2 kJ/mol. Thermodynamic parameters, i.e., δG 0 , δS 0 and δH 0 , were also calculated, with the sorption process being shown to be endothermic.